Permanent Disability Rating Determination and Clinical Regulation: Evaluation of Cases of Muğla Sıtkı Koçman University, Medical Faculty, Forensic Medicine Department - Kadı, Mehmet Resul; Kadı, Gülsüm; Balcı, Yasemin; Göçeoğlu, Ümit Ünüvar (The Bulletin of Legal Medicine, 2018)
Objective: Evaluation of the permanent disability rates and clinical regulation rates of the cases ofMuğla Sıtkı Koçman University, Medical Faculty, Forensic Medicine Department. Which disabilities are appraised and the rate of appreciation are revealed. The aim is to determine the limitations of the relevant Regulation in the application and to develop suggestions.Materials and Methods: Between June 2015-December 2016, the reports of 259 patients who applied for disability rate determination by claiming permanent disability after a traffic accident were retrospectively evaluated. Age, gender, time between accident and medical report, disability distribution, recovery periods, which disability appraisal was applied and the discretion rates were examined. In the data analysis, descriptive statistics were used in which percentage, ratio, mean values were given. A total of 73 disabled cases (23.1%) were assessed with discretion. The disability and appraisal levels of appraisal cases are discussed in detail and the limitations of the relevant regulation were tried to be revealed.Results: 182 (70.3%) males and 77 (29.7%) females out of 259 cases who reported loss of strength in the profession according to Regulation of Permanent Disabilities. Most of the cases (45.2%) were in the 20-39-age group. The time between the accident date and the last inspection date ranged from 1 to 111 months.Discussion: It is a limitation of the relevant Regulation that rates are not determined according to different clinical situations. We think it is necessary to revise the permanent disability rating scale by taking into consideration the current treatment approaches and a comprehensive...
Keywords: forensic medicine; permanent disability; regulation of permanent disabilities; disability appraisal; traffic accident